Comfort for an afflicted conscience: wherein is contained both consolation and instruction for the sicke, against the fearefull apprehension of their sinnes, of death, of the diuell, of the curse of the law, and of the anger and iudgement of God. / Written by M. Iohn de L'Espine, and translated out of French into English by Peter Allibond, minister of the word of God. [electronic resource] : (1591)
Summary goes here